Non‑Metric Data in Household Durable Goods Analysis. Selected Aspects - Dziechciarz, Józef; Dziechciarz-Duda, Marta (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
Measurement of household endowment with durables is crucial in many aspects of assessing the social and economic situation of a country and its citizens. The demand (sales) for durables is regarded as one of the key indicators of economic conditions. Similarly, analysis and evaluation of household durable goods are usually considered in the context of measuring the quality of life. The possession of durables is measured by means of the number and quality of goods in households. Measurement of household endowment is conducted usually by means of weak measurement scales, namely nominal and ordinal. Such data require the use of specialised tools for analysis and modelling. This study discusses the possibilities of statistical analysis of such data. Additionally, modelling and problems of inference on the basis of obtained results are discussed.